The association between hospitalisation for childhood head injury and academic performance: evidence from a population e-cohort study - Gabbe, Belinda J (BMJ Publishing Group, 2014)
BACKGROUND: Childhood head injury has the potential for lifelong disability and burden. This study aimed to establish the association between admission to hospital for childhood head injury and early academic performance. METHODS: The Wales Electronic Cohort for Children (WECC) study is comprised of record-linked routinely collected data, on all children born or residing in Wales. Anonymous linking fields are used to link child and maternal health, environment and education records. Data from WECC were extracted for children born between September 1998 and August 2001. A Generalised Estimating Equation model, adjusted for clustering based on the maternal identifier as well as other key confounders, was used to establish the association between childhood head injury and performance on the Key Stage 1 (KS1) National Curriculum assessment administered to children aged 5–7 years. Head injury was defined as an emergency admission for >24 h for concussion, skull fracture or intracranial injury prior to KS1 assessment. RESULTS: Of the 101 892 eligible children, KS1 results were available for 90 661 (89%), and 290 had sustained a head injury. Children who sustained an intracranial injury demonstrated significantly lower adjusted odds of achieving a satisfactory KS1 result than children who had not been admitted to hospital for head injury (adjusted OR 0.46, 95% CI 0.30 to 0.72). CONCLUSIONS: The findings of this population e-cohort study quantify the impact of head injury on academic performance, highlighting the need for enhanced head injury prevention strategies. The results have implications for the care and rehabilitation of children admitted to hospital with head injury.